Predicting depressions with child abuse potential among career parents in Melaka, Malaysia - Perveen, Asma (Universiti Pendidikan Sultan Idris, 2018)
Predicting depressions with child abuse potential among career parents in Melaka, Malaysia by Perveen, Asma